Indecipherable Chaos: A Cultural Study of Churchill’s Mad Forest - Mohammed, Rebwar Zainalddin; Ali, Darya Dler (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The dramatists and literary men constantly make all their efforts to highlight the negative aspects in the societies and encourage the audiences to disgust them. One of the major issues that has been tackled by the dramatists is war. This study explores the consequences of war and chaos on social lives of the people and is examined in relation to the socio-political context which is contextualized by the playwright to show new example of the insidious institutional power. The focus is on the mass surveillance and data collection against the potential ethical questions it raises along with taking power from those same overseers. This introduces another panoptic principle that the study looks at, while panopticism is hierarchic, there is no one at the top of the hierarchy. The managers are controlled by their plant systems the same way the workers are, and in the wider panoptic sense, even those that are on the outside watching are still being watched by someone higher up the chain of command. Anyone who is ostensibly at the top still has expectations projected onto them and must modify their behavior in certain ways to conform to those expectations.This paper is about Caryl Churchill’s play Mad Forest which sheds light on the Romanian revolution on 16th to 25th December 1989. The play presents the Romanian society before, during, and after the revolution. Meanwhile it focuses on the lives of two families who are Vladu Family and Antonescue Family.